DECLARATIVE CONSTANT POLARITY TAG QUESTIONS: AN ANALYSIS OF SYNTAX AND SEMANTICS - Dianita Damayanti (JEPAL (Journal of English Pedagogy and Applied Linguistics), 2022)
This research focused on the forms and meanings of the declarative constant polarity tag in spoken American English. Therefore, this study was conducted quantitatively in the form of a descriptive analysis of the use of form-tag questions in American English. The data was taken from the spoken component of the American television sitcom created by David Crane and Marta Kauffman, which aired on NBC from September 22, 1994, to May 6, 2004, lasting ten seasons. There are over 158 constant polarity tag questions in spoken English. The results concerning the form of the verb be and the subject it belongs to are mostly used in the tag question. The meanings of declarative constant polarity signify a higher use of "doubt" tags involving interlocutors in American English conversation. Declarative constant tag questions are interesting points to be researched on a wider scope by using more sorts of them in formal conversation.